Vulnerabilidade e proteção da mulher no mercado de trabalho : redução da jornada de trabalho para as empregadas mães atípicas - Almeida, Elene Cristina Martins de (2024)
The present dissertation work entitled “Vulnerability and protection of women in the labor market: reduction of working hours for employees who are atypical mothers” aims to deepen studies regarding the position of women in the labor market, especially women who are atypical mothers. Deepen the sexual division of labor and the responsibilities of men and women towards society. Analyze the social and work scenario in which the atypical mother is inserted, pointing out the bottlenecks that hinder her insertion, permanence and promotion in the job market. The study aims to address the responsibilities regarding guaranteeing the rights of people with disabilities and atypical mother employees in a vulnerable condition caused by responsibilities related to domestic service and care for people, and finally, work on hypotheses that can positively collaborate with the current scenario in order to provide more opportunities for atypical mother employees. The equality of opportunities pursued in this research aims to position human beings at starting points consistent with their realities, thus enabling them to reach opportunities in working life, in search of equality for all human beings regardless of sex. The present study seeks to work rationally on the hypotheses that can in fact be pursued to contribute positively, and without extremism, to women's struggle to recognize their overload in terms of domestic work and caring for people and the effects on their professional life.